Tree-ring climate response of chir-pine (Pinus roxburghii Sarg.) in the sub-tropical forest, western Nepal - Rachana Bhandari; Bijay Pandeya; Balkrishna Ghimire (Acta Botânica Brasílica, 2024)
ABSTRACT A dendrochronological study was carried out to investigate the relationship between the growth of chir pine (Pinus roxburghii) and climatic variables in the subtropical forest of western Nepal.Using tree ring analysis and meteorological data gathered from a nearby meteorological station, a 78-year (1944 to 2021) long chronology has been created. Temperature and precipitation were found to have a substantial impact on P. roxburghii radial growth. Although there were positive correlations between precipitation and tree growth in January, December, and February to April, these relationships were not statistically significant. According to the correlation analyses, there was a negative relationship between the tree growth and the precipitation in September and August of the current year as well as the September of the previous year. Notably, temperature was crucial, as there were significant positive relations found between the minimum and maximum temperatures and tree growth. The temperature of the previous year (September, November, and December) as well as the current year (June to November) had a positive correlation with the growth of tree rings. The results indicated that while temperature was favorable for chir pine radial growth practically all months and seasons, summer to post-monsoon precipitation limited tree growth. Furthermore, the increasing average minimum temperature had a more significant relation with the tree ring growth than the average maximum temperature. Our result demonstrated that the growth of subtropicalP. roxburghiiresponded positively to the present scenario of rising temperature and falling precipitation in the study area. This research contributes valuable insights into the complex dynamics of forest ecosystems and their responses to changing environmental conditions.